Knowledge of the nursing team of maternal infant units concerning genetic disorders - Valquiria Maria de Paula Cunha; Roseane Lopes da Silva Grecco; Sueli Riul da Silva; Marly Aparecida Spadotto Balar (Rev Rene)
The advances in Human Genetics are revolutionizing the understanding of health-illness, becoming a challenge and an impact on the expansion of the nursing role. The objective of this study was to identify the knowledge of the nursing team concerning the genetic abnormalities. This is an exploratory-descriptive and cross-sectional study accomplished through interviews with 171 professionals of the nursing team of the maternal-infant sectors. The majority of the interviewees informed to be able to recognize a genetic syndrome, among which the most known was the Down syndrome. However, most of them couldn’t say for sure which support would be necessary in such cases. It is observed the lack of preparation of the team to approach the family of the children with genetic abnormalities and the need of training in this field.